PENGARUH KINERJA KARYAWAN, PENGELOLAAN, DAN PELAYANAN AIR BERSIH HIPPAMS DALAM MENINGKATKAN KEPUASAN MASYARAKAT (Studi Desa Tlanak Kecamatan Kedungpring Kabupaten Lamongan) - Rahalis, Yoan Inggarjana; Syaikhudin, Ahmad Yani; Sulistyowoati, Anjar (J-EEMB (Journal of Economic Entrepreneurship and Management Business), 2025)
This research aims to determine the influence of employee performance, management, and clean water service provided by HIPPAMS on community satisfaction levels in Tlanak Village, Kedungpring District, Lamongan Regency. The study is based on the importance of clean water access as a basic human need and the strategic role of HIPPAMS as a clean water provider in rural areas not yet covered by PDAM. The research employs a descriptive quantitative approach using surveys and questionnaires distributed to 9 HIPPAMS administrators. Data analysis is conducted with SPSS using validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The findings reveal that employee performance, management, and service significantly affect community satisfaction both simultaneously and partially. Among the variables, service has the most dominant effect on improving community satisfaction. The study provides recommendations for HIPPAMS to continue enhancing the quality of clean water services to ensure public satisfaction and well-being.